Implementing Project-Based Learning in the Independent Curriculum: Insights from Teachers’ Perspectives - Phunyal , Balkrishna (THE ACADEMIA, 2026)
The central aim of this study was to investigate teachers’ perceptions of Project-Based Learning (Project Based Learning) as a pedagogical strategy within the Independent Curriculum framework. The research focused on three main aspects: teachers’ understanding of Project Based Learning concepts, its application in classroom practices, and its influence on student motivation and learning outcomes. To achieve these objectives, a descriptive quantitative design was adopted, targeting teachers who were directly engaged in implementing the Independent Curriculum. Using purposive sampling, a total of 102 teachers were selected. Data were gathered through a structured Likert-scale questionnaire, which was divided into three sections: conceptual knowledge of Project Based Learning, classroom practices, and its perceived impact on students. Analysis was carried out using spreadsheet formulas in WPS Office to provide descriptive insights. Findings revealed that teachers generally hold a positive outlook toward Project Based Learning. A significant proportion (98.20%) demonstrated strong theoretical knowledge of its principles. Teachers also highlighted its benefits, particularly in fostering collaboration (94.12%), motivation (94.12%), and critical thinking (88.24%). However, a gap emerged between knowledge and practice. While teachers understood the principles, actual classroom application especially the integration of multiple subjects proved challenging, with only 78.43% expressing confidence in this area. The study concludes that although teachers are well-acquainted with Project Based Learning concepts, practical challenges hinder full implementation. This underscores the importance of professional development programs that not only deepen theoretical understanding but also equip teachers with practical strategies for interdisciplinary integration. Strengthening these areas is vital for maximizing student engagement and achieving the broader objectives of the Independent Curriculum.